2012
DOI: 10.1177/183693911203700211
|View full text |Cite
|
Sign up to set email alerts
|

The association between playgroup participation, learning competence and social-emotional wellbeing for children aged four–five years in Australia

Abstract: DATA FROM Growing Up in Australia: The Longitudinal Study of Australian Children is used to examine the associations between playgroup participation and the outcomes for children aged four to five years. Controlling for a range of socioeconomic and family characteristics, playgroup participation from birth to three years was used to predict learning competence and social-emotional functioning outcomes at age four–five years. For learning competence, both boys and girls from disadvantaged families scored three–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 17 publications
2
41
1
Order By: Relevance
“…Rates of playgroup participation reported by Aboriginal and Torres Strait Islander parents in this study are lower than the participation rates for Australian children as a whole. Hancock et al (2012) reported that over 50% of Australian children had attended a playgroup or other parent-child group at 2-3 years of age, compared with 23-28% of children in the current study. Issues of reach and retention for more socially disadvantaged families are recognized as a challenge in order to make playgroups a more effective parenting support programme Robinson et al 2011).…”
Section: Discussioncontrasting
confidence: 52%
“…Rates of playgroup participation reported by Aboriginal and Torres Strait Islander parents in this study are lower than the participation rates for Australian children as a whole. Hancock et al (2012) reported that over 50% of Australian children had attended a playgroup or other parent-child group at 2-3 years of age, compared with 23-28% of children in the current study. Issues of reach and retention for more socially disadvantaged families are recognized as a challenge in order to make playgroups a more effective parenting support programme Robinson et al 2011).…”
Section: Discussioncontrasting
confidence: 52%
“…Book reading is a proximal measure of the home learning environment and is associated with variation in language abilities and foundational literacy and numeracy abilities [43] [38]. Playgroup attendance was included based on prior evidence of an association between attending playgroup and better learning (including verbal) outcomes for children growing up in disadvantaged families [44]. Hours in child care was included in our model because a high proportion of children (28%) in our sample spent more than 4 hours a day in non-parental care, during the working week.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large number of families accessing playgroups, research on the benefits that community playgroups provide is limited. Most research has focused on the benefits for children, and it is only recently that wider benefits have been examined . These studies focus on the social benefits for parents and playgroups as sites for health promotion interventions .…”
Section: Introductionmentioning
confidence: 99%